The Influence of Perceived Benefits and Security of QRIS Use on Behavioral Intentions - Risya Zahrotul Firdaus; Yoshua Ardy Putra; Titik Purwinarti; Yulita Tri Haryani; Arizal Putra Pratama; Ridwan Roy Tutupoho; Ratri Kurniasari; Yanita Ella Nilla Chandra (Jurnal Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to find out the development of the useÂ  of Quick Response Code Indonesian Standard (QRIS) as a digital payment method in Indonesia.This study uses the Technology Acceptance Model (TAM) to analyze the acceptance and use of QRIS among users. Data were obtained from literature studies and secondary data related to the development of QRIS in IndonesiaThe findings show that QRIS is well accepted by the general public, especially MSMEs, as a modern, fast, simple, secure, and reliable digital payment method. This is evidenced by a significant increase in the number of users and the value of QRIS transactions in Indonesia.QRIS has become an important part of the digital and financial payment ecosystem in Indonesia.The use of QRIS makes payments easier, faster, and safer for both consumers and business stakeholders, especially MSMEs. Of course, this will support Indonesia's increasingly digitized economy and contribute to the development of the country's digital economy.Further research is needed to explore the long-term impact of the use of QRIS and identify the factors influencing the adoption and use of QRIS in Indonesian society, in line with digitalization trends and changing preferences of business people.The contribution of this research can provide an overview that the use of QRIS as a means of payment can increase the effectiveness and efficiency in the payment system.